Analisis Dan Perancangan Sistem Informasi Simpan Pinjam Berbasis Android Pada Koperasi Bina Usaha Muda Jambi - Hamzah, Kamandanu; Assegaff, Setiawan (LPPM Universitas Dinamika Bangsa, 2020)
Bina Usaha Muda Jambi Cooperative is one of the cooperative organizations whose main activity is providing savings and loan services for its members. The business sector managed in Bina Usaha Muda Jambi Cooperative still uses a manual method in which all member data and transactions are only done by hand and are stored in the book. Resulting in a variety of problems, among others, frequent inconsistencies and redundancy of data, as well as the length of the process of searching and accessing data/information. And for the members of the Bina Usaha Muda Jambi Cooperative who live far away and busy, have their own constraints in knowing the status or notification of information services in Bina Usaha Muda Jambi cooperative. The purpose of this research is to analyze the Saving and Loan information system ain the Bina Usaha Muda Jambi Cooperative and design an Android-Based Saving and Loan information system in the Bina Usaha Muda Jambi Cooperative. In designing this saving and loan cooperative information system using the UML (Unified Modeling Language) modeling language, namely use case diagram, activity diagram, and class diagram. And in making the saving and loan cooperative information system interface using Balsamiq mockups. This research produced a prototype of an android-based saving and loan information system in the Bina Usaha Muda Jambi Cooperative which is expected to overcome problems both in terms of data processing, information distribution (notification) to members and all interested parties, as well as in terms of searching and accessing data/information.